Consistent Risk Management in a Changing World: Risk Equivalence in Fisheries and Other Human Activities Affecting Marine Resources and Ecosystems - Roux, Marie-Julie; Duplisea, Daniel E.; Hunter, Karen L.; Rice, Jake (Frontiers in Climate, 2022)
A changing climate makes the evaluation of human impacts on natural systems increasingly uncertain and affects the risk associated with management decisions. This influences both the achievability and meaning of marine conservation and resource management objectives. A risk-based framework that includes a risk equivalence approach in the evaluation of the potential consequences from human activity, can be a powerful tool for timely and consistent handling of environmental considerations in management advice. Risk equivalence permits a formal treatment of all sources of uncertainty, such that objectives-based management decisions can be maintained within acceptable risk levels and deliver outcomes consistent with expectations. There are two pathways to risk equivalence that can be used to account for the short-term and longer-term impacts of a changing environment: adjusting the degree of exposure to human pressure and adjusting the reference levels used to measure the risk. The first uses existing data and knowledge to derive risk conditioning factors applied to condition management advice on environmental departures from baseline conditions. The second is used to formalise the review and update of management objectives, reference levels and risk tolerances, so they remain consistent with potential consequences from human activity under new biological, ecological and socio-economic realities. A risk equivalence approach is about adapting existing practice to frame environmental considerations within objectives-based risk frameworks, systematically exploring alternative scenarios and assumptions, and conditioning management advice on environmental status. It is applicable to the management of all human activities impacting biological and ecological systems. Concepts of risk, risk conditioning factors, and incremental changes in risk, provide a common currency for the inclusion and communication of environmental effects into advice. Risk equivalence can ensure timely delivery of robust management advice accounting for demonstrated, anticipated or projected environmental effects. This can guide management decisions in a changing world, and greatly facilitate the implementation of an ecosystem approach for the management of human activities.